Pemilihan Kepala Daerah Melalui Pemungutan Suara Ulang dalam Perspektif Fikih Siyasah - Taufiq Alhadi Nasution; Abdullah Abdullah (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2022)
Analysis of the Constitutional Court Decision Number 37/PHP.BUP-XIX/2021 because there was a violation in the regional head election process so that a repeat voting was necessary at 16 polling places at 16 TPS in Labuhan Batu Selatan Regency, and KPPS Performance in Organizers Regional Head Election Seen from the Perspective of Siyasah Jurisprudence. This research is Juridical Empirical. Data collection methods used in this study are observation, interviews, and documentation. The results of the study are that serial number 02 won again from the re-voting in 2021, where serial number 02 was previously in the local elections in 2020, serial number 02 received the most votes. and the plaintiff pair number 02 could not outperform it. The siyasa fiqh review of the performance of the voting organizer group (KPPS) in regional head elections (PILKADA) has not fully proceeded in accordance with siyasa fiqh. because there are still voting organizer groups who are not fully responsible for their work because there are still negligence committed while on duty in holding regional head elections.